Event management handbook - Romero, Eloisa A. (Manila, 2009)
This book aims to provide teachers, students and aspiring event professionals in the philippines with a comprehensive and easy-to-understand workbook on meeting, incentives, conventions and exhibitions (MICE) management
Keywords: Special events - Management - Handbook; Special events - Planning - Handbooks